Verba Aktivitas Bajalan berjalan dan Verba Peristiwa Transisional Ranjah Tabrak dalam Bahasa Banjar - Rissari Yayuk (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
This study discusses bajalan walkactivity verb and verb transitional events transisional ranjah "hit" in the language of Banjarese. Issues discussed included how to form verbs bajalan activity "walk" and verb transitional events ranjah "hit" in banjar.This study aims to describe the activities bajalan verb "walk" and verb transitional events ranjah "hit" in the language banjarese. The method used in this study was descriptive qualitative method. Techniques used in the data acquisition techniques involved capably refer free. There are three action steps based methods and techniques, namely the collection, analysis and presentation of data. Data were collected from 2016 1 Januari s.d. March 1, 2016 in the village of Bakarung, Hulu Sungai Selatan, South Kalimantan Province. based on the results penenelitian bajalan activity verb "walk" in the language of Banjarese show in terms of function predicate position, in terms of the meaning of declared activities subject intentionally, and syntax can be used as a messenger or imperative word. While Verb transitional events ranjah "hit" in the language banjarese show in terms of function predicate position, in terms of meaning describes the displacement state of the subject inadvertently, in terms of syntax can not be used as a sentence order, or imperative.